PENGARUH PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA - Lilis Lela Sandy; Suryadi -; Anton Nasrullah (Jurnal Penelitian Bimbingan dan Konseling, 2017)
The decline in student achievement in school is the effect of the lack of attention of parents so that significantly low student learning motivation. The research objectives are; 1) to determine the influence of parents attention on improving student achievement in school. 2) to know the influence of learning motivation to improve student learning. 3) to simultaneously influence the influence of parents' attention and motivation to learn to improve learning achievement. 4) to know the correlation between parental attention and learning motivation to improve student achievement. The method used is descriptive verification method with ex post facto and survey approach. The instruments used are questionnaires distributed to students. The results of this research are; 1) there is influence of parent attention to improvement of student achievement in school. 2) there is influence of learning motivation to improve student learning. 3) there is influence simultaneously influence of parent attention and motivation learn to increase learning achievement. 4) there is a correlation between the attention of parents and the motivation to learn to improve student achievement. Keywords: Parents' attention, learning motivation, learning achievement